Assessment of genetic ancestry and population substructure in Costa Rica by analysis of individuals with a familial history of mental disorder - Segura Wang, Maia (2010)
The population of Costa Rica has been considered valuable for locating susceptibility genes of complex disorders because of historical events and a gradual admixture process. We present an assessment of 426 unrelated individuals with a familial history of mental disorder and with ancestors born in the Central Valley, genotyped at 730 microsatellites to evaluate genetic diversity, ancestry, and substructure at the general and regional population levels using quantitative methods. Low population substructure was found. Estimated mean ancestry proportions were 54%, 32%, and 13% for European, Amerindian, and African components, respectively, with some regional variation. The F(ST) values obtained confirm the largest genetic similarity to Europeans. Subdivision of the Amerindians into individual populations revealed strong similarity to Chibchan groups. Analysis of the African ancestry showed high similarity to West and Central African populations. Gene ancestries from other African areas were also detected, probably resulting from ancestral admixture within Africa prior to colonial times. Our analyses show, in an ethnohistorical-genetic context, that gene flow and admixture are important components of Costa Rican population history. The results confirm the need to consider the particular regional genetic structure, the effects of genetic drift and the ancestry when designing and interpreting investigations of genetic traits in this population.